Validity of Dietary Assessment Methods When Compared to the Method of Doubly Labeled Water: A Systematic Review in Adults - Burrows, Tracy L.; Ho, Yan Yee; Rollo, Megan E.; Collins, Clare E. (Frontiers in Endocrinology, 2019)
Accuracy in quantifying energy intake from measurements of diet using common dietary assessment methods is crucial for interpreting the relationship between diet and chronic disease. The aim of this systematic review was to evaluate the validity of dietary assessment methods used to estimate the daily energy intake (EI) of adults in comparison to total energy expenditure (TEE) measured by doubly labelled water (DLW). Articles published in English across nine electronic databases, published between 1973 and February 2019 were retrieved. Studies were included if participants were adults (≥18 years) and used the DLW technique to measure TEE compared to self-reported EI. A total of 59 studies were included, with a total of 6298 free living adults and a mean of 107 participants per study. The majority of studies reported significant (P < 0.05) underreporting of EI when compared to TEE assessed using DLW, with few over-reporting EI. Sixteen studies assessed EI using a technology method, most commonly (n=10) as a food record. Misreporting was more frequent among females compared to males within recall based dietary assessment methods. The degree of under-reporting was highly variable within studies using the same method, with 24Hr recalls having less variation and degree of under reporting compared to other methods.